'Obligations', Decolonization and Indigenous Rights to Governance. Issue 1 (January 2014) - Christie, Gordon
Abstract : Many contemporary Indigenous communities in Canada assert an ability to make fundamental authoritative decisions about what is acceptable use of their territories. I focus on the question of legal obligations that might befall the Crown in its relationships with these communities and their claims. I argue that any such obligations must be seen as culturally and contextually specific, not only in the sense that particular Crown obligations take on content and form within the context of the culture within which the Canadian legal system has emerged but also in the sense that this non-Indigenous culture and history generate the very meaning of the notion of 'obligation' here at play. This culturally determined meaning functions to make it extremely difficult to make sense of the notion the Crown actually has legal obligations in relation to Indigenous assertions of authority over territories. This suggests decolonization in this context should be focused on discursive colonization and its undoing. Along those lines I offer a sketch of what 'legal obligation' might mean in an Indigenous cultural-historical setting. Within this way of understanding the situation, addressing questions of Crown obligations would begin with consideration of Indigenous systems of meaning-generation. Analysis would focus on working out what it means within such normative worlds to determine a party has a legal obligation, and would then turn to what this has to say about legal obligations that might be understood to fall on the Crown. I argue that while the Crown will almost certainly not respond to claims it has legal obligations within what it takes to be separate legal systems, describing the landscape this way paints a truer picture of the world as it presents itself. The landscape has been, and continues to be, one of distinct meaning-generating peoples, each determining what it understands such concepts as 'legal obligations' to mean and entail. The colonial agenda has been for many generations to deny the existence of Indigenous systems, to have Indigenous communities come to think of 'legal obligations' in ways colonial authorities determine. Decolonization – in this form – requires a backing out of these ways of thinking. This article clears away forms of thinking that obstruct our view, giving us all an opportunity to perceive the complex landscape we in fact inhabit.